2023
DOI: 10.3390/children10060934
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dentofacial Features and Bullying from Childhood to Adulthood: A Systematic Review

Abstract: Bullying occurs when an individual is repeatedly victimised by negative actions performed by peers. As oral features, like malocclusion and dental structural defects, can promote psychological distress, which is also found in those who are bullied, we aimed to study the association between orofacial conditions and bullying. A systematic review (PROSPERO CRD42022331693), including articles dealing with bullying and dentofacial traits, was performed following the PRISMA chart. The iterative search of eligible pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A systematic review which included 25 studies found that the majority of studies (88%) showed a link between malocclusion or dental structural defects and exposure to bullying among young adolescents [9].…”
Section: High-risk Populationsmentioning
confidence: 99%
“…A systematic review which included 25 studies found that the majority of studies (88%) showed a link between malocclusion or dental structural defects and exposure to bullying among young adolescents [9].…”
Section: High-risk Populationsmentioning
confidence: 99%